Lipomatosis Incidence and Characteristics in an Italian Cohort of Mitochondrial Patients - Musumeci, Olimpia; Barca, Emanuele; Lamperti, Costanza; Servidei, Serenella; Comi, Giacomo Pietro; Moggio, Maurizio; Mongini, Tiziana; Siciliano, Gabriele; Filosto, Massimiliano; Pegoraro, Elena; Primiano, Guido; Ronchi, Dario; et al. (Frontiers in Neurology, 2019)
Lipomas have often been associated with mtDNA mutations and were mainly observed in patients with mutation in mitochondrial tRNAlysine which is also the most frequent mutation associated with MERRF. Up to date, no systematic studies have been developed in order to assess the incidence of lipomas in large cohorts of mitochondrial patients.The aim of this study is to analyze the incidence and characteristics of lipomas among an Italian cohort of patients with mitochondrial diseases. A retrospective, database-based study (Nation-wide Italian Collaborative Network of Mitochondrial Diseases) of patients with lipomas was performed. A total of 22 (1.7%) patients with lipomas have been identified among the 1,300 mitochondrial patients, enrolled in the Italian database. In about 18% multiple systemic lipomatosis (MSL) was the only clinical manifestation; 54% of patients showed a classical MERRF syndrome. Myopathy, alone or in association with other symptoms, was found in 27% of patients. Lactate was elevated in all the 12 patients in which was measured. Muscle biopsy was available in 18/22 patients: in all of them mitochondrial abnormalities were present. Eighty six percent had mutations in mtDNA coding for tRNA lysine. In most of patients, lipomas were localized along the cervical-cranial-thoracic region. In 68% of the patients were distributed symmetrically. Only two patients had lipomas in a single anatomical site (1 in right arm and 1 in gluteus maximum). MSL is often overlooked by clinicians in patients with mitochondrial diseases where the clinical picture could be dominated by a severe multi-systemic involvement. Our data confirmed that MSL is a rare sign of mitochondrial disease with a strong association between multiple lipomas and lysine tRNA mutations. MSL could be considered, even if rare, a red flag for mitochondrial disorders, even in patients with an apparently isolated MSL.